09 Bioethics in terms of christian morality - Ștefan-Adrian ANDRIEȘ (Association of Social and Educational Innovation, 2015)
The moral action of the individual is directly proportional to his ideal or the transcendent experiences of the human species. Ethical actions most often have a decisive impact on the society and hence on the personal identity.The aim of this paper is to identify the relationship between the external action of the pragmatic and the culmination of the inner feelings of the individual, that provide the intensity of the prevalence of the essence of morality over the whole human edifice. The essay of a society's actions is determined by arranging in an intellectual system all the religious events that bring the most intelligent species to a contradiction with its own identity in a limited system and most often with an impression of fatality regarding the existence. The erosion of altruism in the human consciousness entails the destruction of the entire basis that underlies the creation of the society and the individual as a person that is able to access a mystical type of knowledge, namely an extension of all his actions. We would like to show that the life of the society and the individual in collaboration with his own ego manages the historical events both at social as well as personal scale, and the interest in a Christian morality is the real itinerary of a personduring the entire existence.